2010
DOI: 10.1007/s12034-010-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electromechanical properties of PLZT x/57/43 ceramics

Abstract: The compositions of lead lanthanum zirconate titanate PLZT [Pb(Zr 0⋅57 Ti 0⋅43 )O 3 + x at% of La, where x = 3, 5, 6, 10 and 12] have been synthesized using mixed oxide route. The temperature dependent electromechanical parameters have been determined using vector impedance spectroscopy (VIS). The charge constant d 31 and elastic compliance s E 11 show a peak in all the samples at a temperature T mt much below the ferroelectric -paraelectric transition temperature, whereas the series resonance frequency f s sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, the commercial PZT ceramics generally have a Curie temperature (T c ) much \380°C. The corresponding safe operating temperatures are generally limited to a half of their T c to ensure the stability of piezoelectric properties [6][7][8][9][10][11][12]. Therefore, PZT-based ceramics are hard to meet the practical requirements for the high-temperature piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the commercial PZT ceramics generally have a Curie temperature (T c ) much \380°C. The corresponding safe operating temperatures are generally limited to a half of their T c to ensure the stability of piezoelectric properties [6][7][8][9][10][11][12]. Therefore, PZT-based ceramics are hard to meet the practical requirements for the high-temperature piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that PLZT offers excellent electromechanical property of high electromechanical coupling coefficient parallel with high density, electrical permittivity, and low dielectric losses [1,2]. Among the wide range of shapes and forms, the ceramics microfibers are * proposed to have a higher performance in laminate multiferroic composites.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of a phenomenological model with restricted drift motion of charged particles, Volkov et al (2003) described the universal dynamic response and broad band relaxation considering Maxwell-Wagner type interaction between conducting clusters of relaxors like PLZTs. The room temperature dielectric response of PLZT x/57/43 and Cr-doped PLZT 6/57/43 and temperature dependent piezoelectric response of PLZT x/57/43 have been investigated by us and it is found that the a.c. conductivity of these compositions follows the universal dielectric response (Jonscher 1977;Shukla et al 2004Shukla et al , 2006Shukla et al , 2010. Reviews by Buixaderas et al (2004) and Bokov and Ye (2006) describe various features of perovskite relaxors such as PLZTs and a variety of observations are attributed to the presence of polar nanoregions in the material.…”
Section: Introductionmentioning
confidence: 99%